Matriks Kabur dan Karakteristiknya - Muhammad Abdy; Maya Sari Wahyuni; Muh. Hadi Purnomo (Jurusan Matematika FMIPA UNM, 2019)
This research examines the definitions, operations, and theorems of fuzzy matrices and their characteristics. The literature used as a reference is an article written by Pal (2016), Sidky & Emam (1992), and Suroto & Wardayani (2015). The results can be given improvements to the operations used in the fuzzy matrix and the set of square fuzzy matrix theorems can be extended to fuzzy matrix set theorems. In addition, it was concluded that the set of square fazzy matrix fulfilled the algebraic properties for semigroup and semiring. But it does not fulfill algebraic properties for groups and rings.